Volume alteration of undescended testes: Before and after orchiopexy - Chi-Shin Tseng; Kuo-How Huang; Yeong-Shiau Pu; I-Ni Chiang (Urological Science, 2016)
Objectives: We used ultrasound to investigate the volume of undescended testes before and after orchiopexy, and compared these data with normally descended testes. Materials and Methods: We retrospectively reviewed boys in the age range of 0–18 years who had undergone unilateral or bilateral orchiopexy due to undescended testes (International Classification of Diseases-Ninth Revision, ICD-9 752.51) in National Taiwan University Hospital, Taipei, Taiwan between January 2010 and December 2013. A total of 116 boys received preoperative testicular ultrasound evaluation, and 75 of them received regular ultrasound during a mean follow-up period of 2.5 years. The volume of the testes was calculated by applying Hansen formula [testicular volume = length (L) × width (W)2 × 0.52] and compared with a cohort of 92 boys constructed for normative values of testicular volume from The Netherlands. Results: The mean volume of the 145 undescended testes among 118 boys was 0.238 mL. The volume of the undescended testes was significantly smaller (p < 0.001) than the mean normative value of 0.418 mL. The volume of postorchiopexy undescended testes (0.356 mL) revealed a growing trend in the mean 2.5-year follow-up with a significance increase of size (p = 0.001), but has not yet reached the normal testicular size (0.604 mL). Conclusion: The preorchiopexy volumes of undescended testes are significantly smaller than normative values. The follow-up postorchiopexy volumes of undescended testes actually increased in size, although they were still smaller than normative values. These Taiwanese testicular growth curves should become reference values in pediatric clinical practice when evaluating testicular development. Keywords: cryptorchidism, orchiopexy, testicular volume, treatment outcome, undescended testis